Cementation procedures for casted postcores - Mercuri, Patricia A.; Tangco, Aregico D.
Since all types of posts, whether casted or preformed, gain their retention by cementation, a study was done to observe whether or nor any differences occurred among three cementation, procedures in relation to cement distribution, proper seating of the postcore and presence of cement beyond the postcore. Canines and casted postcores were utilized and ZnPO4 cement was either coated on the post, inserted into the canal or a combination of both, were done together. the results showed that these was no significant difference in cement distribution, postcore seating or presence of cement beyond the post and therefore retention should be the same for all.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Prosthodontics; Cementation procedures